Un estudio sobre el groupware; propuesta de fundamentación teórica para el diseño de actividades colaborativas usando moodle. - Pérez, O.; Rangel, N.; González, A.; Fagúndez, T. (Revista Cubana de Física, 2007)
Taking advantage of the communicative potential of Internet the interaction possibilities improve dramatically. This improvement has a direct repercussion in the work aid and a better facility to the coordination of work, related in group activities. For this coordination is also required a technical infrastructure that supports the requirements of such activities. The work that is presented is positioned along to the lines of the investigation of collaborative learning with computer network mediation. The type of the investigation is a qualitative. It's comprised a bibliographic revision on applications of groupware in education with environments collaborative, their tools, and evaluations of these environments and in special those based on moodle. The relevance of this investigation is to find bases for the successfully design of an educational module directed to university physics' students, under platform offered for the virtual classroom of Engineering Faculty in the Universidad de Carabobo - Venezuela, based on environments collaborative, using moodle.